Inorganic Polymers Semiconductor Materials (Chemical and Structure Modification of Polymers, 2015)
Abstract ... 125 10.1 Introduction ... 126 10.2 Experimental Part ... 128 10.3 Results and Discussions ... 129 10.4 Conclusion ... 129 Keywords ... 129 References ... 129ABSTRACTMetaphosphates alkali metals of inorganic polymers, which in the molten state retain polymer structure as electrolytes with high ionic conductivity and have a substantially viscosity.